Cumplimiento tributario y el desarrollo de las mypes en el distrito de Ucayali Contamana 2023 - Romero Labajos, Wuirlle (2023)
The research had as study objective, to determine the relationship between tax compliance and the development of Mypes in the District of Ucayali Contamana 2023, using a descriptive-correlational study with a non-experimental design; made up of a population and sample of 86 Mypes, to whom a survey was applied for data collection. therefore, tax compliance is high, because the companies agree because they almost always know the income limit to qualify for a tax regime; as he is also almost always aware that he can be fined for not complying with his tax obligations. On the other hand, it was identified that the development of the Mypes is qualified as good, since they almost always carry out permanent supervision of the commercial actions of their company; the company's processes are constantly improving; and always in accordance with the reinvestment of profits generated; in accordance with marketing strategies to achieve customer satisfaction and loyalty; but they always have the initiative to lead new projects that generate income for their company. Finally, it was determined that there is a relationship between the study variables, contrasted by a coefficient of 0.719 and a (bilateral) significance of 0.000.